2014
DOI: 10.1093/hmg/ddt671
|View full text |Cite
|
Sign up to set email alerts
|

Germline sequence variants in TGM3 and RGS22 confer risk of basal cell carcinoma

Abstract: To search for new sequence variants that confer risk of cutaneous basal cell carcinoma (BCC), we conducted a genome-wide association study of 38.5 million single nucleotide polymorphisms (SNPs) and small indels identified through whole-genome sequencing of 2230 Icelanders. We imputed genotypes for 4208 BCC patients and 109 408 controls using Illumina SNP chip typing data, carried out association tests and replicated the findings in independent population samples. We found new BCC susceptibility loci at TGM3 (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 38 publications
1
45
0
1
Order By: Relevance
“…Interestingly, significantly decreased expression of RGS22 was found of patients with azoospermia. Taken together, these results indicated that RGS22 protein could be involved in spermatogenesis and concretely in spermiogenesis (Hu et al, 2008(Hu et al, , 2011Stacey et al, 2014).…”
Section: Rgs22 Subfamily Of Rgs Proteinsmentioning
confidence: 62%
“…Interestingly, significantly decreased expression of RGS22 was found of patients with azoospermia. Taken together, these results indicated that RGS22 protein could be involved in spermatogenesis and concretely in spermiogenesis (Hu et al, 2008(Hu et al, , 2011Stacey et al, 2014).…”
Section: Rgs22 Subfamily Of Rgs Proteinsmentioning
confidence: 62%
“…There is also evidence for TGM3 to induce cell proliferation and migration in esophageal cancer by downregulating the NF-κB signaling pathway [33]. Genome-wide association study (GWAS) of 38.5 million SNPs and small indels identified TGM3 variant as a contributor to risk of basal cell carcinoma [34]. The role of TGM3 in small cell lung cancer remains to be established.…”
Section: Resultsmentioning
confidence: 99%
“…We then searched two of the most recent GWAS publications in NCBI PubMed (http://www.ncbi.nlm.nih.gov/pubmed/), using the same keywords (2 SNPs). Of the 70 SNPs discovered during the previous GWAS studies [13181920212223242526], 8 genotyped SNPs and 4 imputed SNPs in independent genes were presented in our genotype data.…”
Section: Methodsmentioning
confidence: 99%